Joint source and relay precoder design for energy‐efficient MIMO‐cognitive relay networks. Issue 15 (1st September 2019) - Maurya, Shikha; Bansal, Matadeen; Trivedi, Aditya
Abstract : This study addresses the energy efficiency (EE) maximisation problem in multi‐input multi‐output cognitive relay networks, where a secondary transmitter–receiver pair communicates through an amplify‐and‐forward relay using the licenced spectrum of a primary user. The authors aim to maximise the EE of the secondary system by jointly designing the source and relay precoding matrices, subject to transmit power, interference, and quality‐of‐service constraints. The resultant problem is non‐convex in the precoding matrices; it is converted into a much simpler vector‐valued problem using singular value decomposition. A combination of iterative optimisation, fractional programming, and Lagrangian multiplier is used to further tackle the problem. Numerical results are presented to evaluate the EE performance of the proposed scheme. Impact of transmit power, interference threshold, and minimum rate requirement on the EE is analysed.